Real-time motion tracking of cognitive Baxter robot based on differential inverse kinematics. (16th June 2021) - Li, Shaobo; Zhang, Xingxing; Yang, Jing; Bai, Qiang; Hu, Jianjun; Song, Qisong; Li, Zhiang
The tracking motion of the robot is realized based on a specific robot or relying on an expensive movement acquisition system. It has the problems of complex control procedures, lack of real-time performance, and difficulty in achieving secondary development. We propose a robot real-time tracking control method based on the control principle of differential inverse kinematics, which fuses the position and joint angle information of the robot's actuators to realize the real-time estimation of the user's movement during the tracking process. The motion coordinates of each joint of the robot are calculated and the coordinate conversion between man and machine is realized with the combination of the Kinect sensor and the robot operating system. We have demonstrated the robustness and accuracy of the tracking method through the real-time tracking experiment of the Baxter robot. Our research has a wide range of application value, such as automatic target recognition, demonstration teaching, and so on. It provides an important reference for the research in the field of cognitive robots.